Physiological nicotine dependence using the Fagerstrom test of nicotine dependence scale in tobacco users visiting tobacco cessation center - Deepak Gurung; Vinay Kumar Bhardwaj; Shailee Fotedar (Muller Journal of Medical Sciences and Research)
Background: The study aimed to assess the physiological dependence of tobacco use among patients visiting the tobacco cessation center (TCC) in the tertiary institute. Methods: A cross-sectional study design with simple random sampling was used. The information obtained from the subject was through interview recorded on a structured pro forma. The information included demographic details, dependence status based on tobacco use history and behavior, and the Fagerstrom test of nicotine dependence (FTND) for physiological dependence. Results: Of the total subjects in the study, 33.2%–37.5% subjects had either high or very high FTNDs score category. The mean FTND score was to be 6.8 ± 2.4. A high or very high FTND score was found for those tobacco users, who switch over to cheaper tobacco products on price rise, daily buyers, craving as reason for relapse, and those subjects who were in the precontemplation stage with a statistically significant difference. 31.3% did not agree that the price increase in tobacco products will decrease tobacco use for subjects starting the initiation of tobacco products in the morning 31–60 min after waking up. The amount of tobacco use was statistically significant for the pattern for purchase of tobacco products and stages of behavior. Conclusion: The physiological nicotine dependence in the study was of high level. Tolerance and withdrawal are important constructs in understanding physiological nicotine dependence using the FTNDs scale. Tolerance was associated with various stages of behavior and pattern of tobacco purchase in the study. Withdrawal was associated with various reasons of quitting tobacco use, stages of behavior, and some price influence on tobacco use. There was a gradual and less withdrawal in low physiological nicotine dependence in the study.